EFFECT OF FINANCIAL DISTRESS, FIRM SIZE, AUDIT FEE, PANDEMIC COVID 19 AND CHANGE IN MANAGEMENT ON AUDITOR SWITCHING (STUDIES OF BANKING COMPANIES LISTED ON FOR THE 2019-2022 PERIOD) - Ramadhan, Alauddin Shidqi; Darsono, Darsono (Diponegoro Journal of Accounting, 2024)
This study investigates the influence of financial distress, firm size, audit fees, the COVID-19 pandemic, and management changes on auditor switching among banking companies listed on the Indonesia Stock Exchange (IDX) during 2019-2022. The primary variable of interest is auditor switching, measured as a dummy variable (0 for no switch, 1 for switch). Independent variables include financial distress (measured by Loan to Deposit Ratio), firm size (natural logarithm of total assets), audit fees, the COVID-19 pandemic, and management changes. Using logistic regression for analysis, the study finds no significant impact of financial distress, firm size, the COVID-19 pandemic, or management changes on auditor switching. However, audit fees have a significant effect, indicating that higher fees increase the likelihood of switching auditors. The research underscores the complexity of auditor switching decisions and provides insights for policymakers and stakeholders in the auditing and corporate sectors.